2011
DOI: 10.1111/j.1365-2516.2011.02685.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective registry of European haemophilia B patients receiving nonacog alfa, recombinant human factor IX, for usual use

Abstract: Nonacog alfa, a recombinant factor IX (FIX) used for the treatment of haemophilia B, was approved in Europe in 1998. In accordance with European Medicines Agency requirements, a registry study was conducted from 2002 to 2009. A reformulated iso-osmotic version was approved for European use in 2007. This study was conducted to evaluate the safety of nonacog alfa in a usual care setting, and provide clinical trial and postmarketing surveillance data support. This open-label, non-interventional, prospective obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…Lastly, Study 101039 (N ¼ 218) was a European registry study conducted in nine countries to evaluate the safety of nonacog alfa in a usual care setting, with a focus on events of special interest (e.g. lack of effect, inhibitor development, thrombosis, red blood cell agglutination, allergic events) [33]. Previously treated or untreated patients receiving original or reformulated nonacog alfa, as well as patients with a history of inhibitor development or allergy to FIX products, were included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, Study 101039 (N ¼ 218) was a European registry study conducted in nine countries to evaluate the safety of nonacog alfa in a usual care setting, with a focus on events of special interest (e.g. lack of effect, inhibitor development, thrombosis, red blood cell agglutination, allergic events) [33]. Previously treated or untreated patients receiving original or reformulated nonacog alfa, as well as patients with a history of inhibitor development or allergy to FIX products, were included.…”
Section: Methodsmentioning
confidence: 99%
“…Eight patients in the registry study (Study 101039) reported allergic manifestations, with three patients experiencing events that were considered serious adverse events; one patient had a history of allergy to plasma-derived replacement products and two patients experienced a de-novo allergy to nonacog alfa. Symptoms in all patients resolved after switching to a plasma-derived product [33]. Five previously untreated patients in Study 300 experienced eight potentially allergic events within 48 h of nonacog alfa infusion, two of which were severe [29].…”
Section: Safetymentioning
confidence: 96%
See 2 more Smart Citations
“…One 71-year-old patient experienced deep venous thrombosis in association with hemostatic therapy after the surgery for spinal stenosis [36]. The registry included PMS data for both the original and reformulated rFIX.…”
Section: Efficacy For Surgical Treatmentmentioning
confidence: 99%